If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 10 = 12 + 4x Reorder the terms: 10 + 6x = 12 + 4x Solving 10 + 6x = 12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 10 + 6x + -4x = 12 + 4x + -4x Combine like terms: 6x + -4x = 2x 10 + 2x = 12 + 4x + -4x Combine like terms: 4x + -4x = 0 10 + 2x = 12 + 0 10 + 2x = 12 Add '-10' to each side of the equation. 10 + -10 + 2x = 12 + -10 Combine like terms: 10 + -10 = 0 0 + 2x = 12 + -10 2x = 12 + -10 Combine like terms: 12 + -10 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| -12=4+v | | 3(2w-4)=18 | | 3x+9=8x-6 | | -4y+9+y=3 | | 2[A+5]=2[2A+3] | | 3x+2y=52 | | 6z=-14 | | 5x-7=15+3x | | 2(x-1)(x+1)=2 | | 5a-(2a-1)=2 | | 5(p+6)=9p | | 2[4M-5]=4M+2 | | x^2+9-9-6x+6x=0 | | x^2+9-6x+6x=0 | | 4[X-3]=3[3X+1] | | x^2+9+6x=0 | | x^2+9-9+6x=0 | | 4x-2=x | | 2[a+5]=2[2A+4] | | 3x+9=8x-3 | | -45=3(4v+1) | | T-9=-5 | | 3+x=5+4x | | 3[x-2]=5[x+4] | | 4x/4=9/4 | | 5b-4=6[b+2] | | -2y+4(-3v-4)=-58 | | -6n-4=4-5n | | -6n-4=4-5n | | -6n-4=4-5n | | 5[x-2]=2x-13 | | -3(4m+6)=3(4-2m) |